2017
DOI: 10.1016/j.tranon.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Acriflavine Inhibits Acquired Drug Resistance by Blocking the Epithelial-to-Mesenchymal Transition and the Unfolded Protein Response

Abstract: Epithelial-to-mesenchymal transition (EMT) is linked to tumor invasion, drug resistance and aggressive disease and this is largely dependent on the cell's microenvironment. Acriflavine (ACF) is an old antibacterial drug recently also suggested as anticancer agent and HIF inhibitor. We wanted to study the effect of acriflavine on EMT in different human cancer models. Pancreatic cancer cells (Panc-1) were exposed to TGF-β1 or cobalt chloride (to mimick severe hypoxia) to induce EMT. For our third model we expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Numerous stress types induce the ISR-regulated ATF4 activation mediated by p-eIF2a (4). The ISR controlled by PERK-GCN2/eIF2a/ATF4 mediates EMT and metastasis (10,11,13), tumorigenesis (9,14), and chemoresistance (16,17). In nonstressing conditions and presence of TGFb1, we found that the ISR did not drive ATF4 expression for all the cell lines tested herein; however, it was important in SUM159PT and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Numerous stress types induce the ISR-regulated ATF4 activation mediated by p-eIF2a (4). The ISR controlled by PERK-GCN2/eIF2a/ATF4 mediates EMT and metastasis (10,11,13), tumorigenesis (9,14), and chemoresistance (16,17). In nonstressing conditions and presence of TGFb1, we found that the ISR did not drive ATF4 expression for all the cell lines tested herein; however, it was important in SUM159PT and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 64%
“…ATF4 is a transcription factor belonging to the ATF/cyclic adenosine monophosphate response element binding protein (ATF/CREB) family, overexpressed in tumors, including breast cancer and TNBC (6)(7)(8). ATF4 regulates tumor growth, autophagy, drug resistance, and metastasis during ISR through PERK and GCN2 pathways (9)(10)(11)(12)(13)(14)(15)(16)(17). Independent of the cellular stress, ATF4 regulates cell metabolism (8,18,19), osteoblast differentiation (20), drug resistance (21), invasion, and metastasis in esophageal squamous cell carcinoma (22).…”
Section: Introductionmentioning
confidence: 99%
“…Increased PERK activity in breast cancer is considered a key feature of cells with an epithelial-to-mesenchymal (EMT)-related phenotype (Feng et al, 2014). Significantly, suppressing the PERK/eIF2a/ ATF4 axis in pancreatic cancer cells using acriflavine led to inhibition of morphological EMT and invasion as well as reversal of acquired drug resistance (Dekervel et al, 2017). eIF2a phosphorylation is also a driver of increased invasiveness in chronic myeloid leukemia (Podszywalow-Bartnicka et al, 2016).…”
Section: Translation Reprogramming and Invasionmentioning
confidence: 99%
“…However, a previous large-scale chemogenetic screen identified ACF as a drug that specifically kills uls1 Δ yeast (26) and we confirmed the potent toxicity of ACF (Fig 1A). ACF has been described as having antibacterial (27), antimalarial (28) and anti-cancer properties (29). This broad range of activity is likely due to the fact that ACF inhibits type II topoisomerase activity in vitro (28, 30).…”
Section: Resultsmentioning
confidence: 99%